THE EFFECT OF ACUPRESSURE TO HEMOGLOBIN LEVELS OF THE ELDERLY - Sholihah, Imrok Atus; Ani, Nur; Sartika, Iik (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: Hemoglobin is a protein in erythrocytes. Anemia in the elderly often goes unnoticed. Traditional Chinese Medicine (TCM) is also considered as one of the complementary and alternative medicine (CAM). This study aims to determine hemoglobin levels after acupressure therapy of the elderly at Panti Griya Sehat Bahagia.Methods: The design of this study used an experimental research design in the form of two groups: pretest-posttest design. The sample in this study were all elderly in Panti Griya Sehat Bahagia. The study was conducted in September 2022 at Panti Griya Sehat Bahagia, Karanganyar Regency. The sampling technique was total sampling of 34 subjects in this research. Data collected is the primary data by recording and evaluating the results of the action in this research. Statistical test using univariate analysis and bivariate analysis by using t test.Results: There were differences in hemoglobin levels before and after acupressure therapy in the elderly at Panti Griya Sehat Bahagia (p<0.001).Conclusion: There is an average increase in hemoglobin levels between before and after acupressure therapy in the elderly at Panti Griya Sehat Bahagia.